Domesday Book and the transformation of English landed society, 1066–86. (26th April 2019) - Baxter, Stephen; Lewis, C. P.
Abstract: This article presents the first fruits of a long-term project which aims to identify all the landholders named in Domesday Book, and to build up a picture of English landed society before and after the Norman conquest. The first part describes the project's methods and illustrates them with a selection of short profiles of individuals whose careers add distinctive colour to the emerging picture. The second offers firstly an analysis of the social distribution of landed wealth in England in 1066 and 1086, quantifying the numbers of landholders in different groups defined by the amount of the land assigned to them in Domesday. We then turn to a spatial analysis of landed society, using maps to illustrate the geographical distribution of landholding. In doing so, we offer fresh perspectives on the transformation of English landed society in the aftermath of conquest.